A study on the effect of treatment using occlusal splint in Juvenile temporomandibular disorders - MIYAOKA, Yoshinao; MIYATA, Takashi; SHIN, Kitetsu; ARAKI, Hisao (Journal of the Japanese Society for the Temporomandibular Joint, 1996)
The purpose of this study was to investigate the clinical effects of treatment by using an occlusal splint in juvenile temporomandibular disorders. The subjects were 30 young patients, who were aged 12-18 years. The results were as follows; 1. The results of the first examination (1) The most frequent of the chief complains of TMJ (Temporomandibular Joint) were TMJ pain (21 subjects, 70.0%) followed by TMJ noise and trismus. (2) The period from the first significant symptoms of TMJ to the first examination was usually within three months. (3) As to the present status in the first examination, 13 subjects (43.3%) complained of TMJ pain combined with TMJ noise and trismus. (4) The frequency of the individual classifications according to The Japanese Society for Temporomandibular joint disorders (1986), were 19 subjects (63.3%) suffered from Type III, 7 subjects (23.4%) from Type II, 2 subjects (6.7%) from Type I and Type I+II. 2. The results of treatment (1) The results and the effects of the splint treatments were examined to ascertain the improvement ratio. TMJ pain was rapidly improved within 10 weeks. TMJ pain was completely improved with in 18 weeks and masticatory muscle pain in 14 weeks. (2) TMJ noise was less readily improved and 3 subjects were able to gain no improvement after a period of 24 weeks. (3) Trismus was completely improved in 14 weeks. (4) The average length of time for trismus improved being 5.6 weeks. The differences in length of time between the averages of improved period on trimsus and TMJ pain and the averages of improved period on trismus and TMJ noise were statistically significant (p<0.05). After conclusive study, results showed that cases that involved trismus took a greater length of time to improve.